The Implementation of E-Filing on Taxpayer Compliance in Ambon City: A Theory of Planned Behavior Approach - Ardhiatul Halima Tuasalamony (Universitas Muhammadiyah Makassar, 2025)
This study examines the influence of e-Filing implementation on taxpayer compliance in Ambon City by applying the Theory of Planned Behavior (TPB) as the analytical framework. TPB explains compliance behavior through three main constructs: attitudes toward behavior, subjective norms, and perceived behavioral control. This research employs a literature review method by collecting and analyzing previous studies from Google Scholar and official taxation sources using keywords such as “e-Filing,” “tax compliance,” and “Theory of Planned Behavior.” After screening for relevance, selected articles were synthesized to identify key determinants of compliance behavior. The review findings indicate that the implementation of e-Filing positively contributes to taxpayer compliance; however, several contextual factors in Ambon still hinder optimal adoption. Limited digital literacy, low awareness of tax obligations, and inadequate internet infrastructure in certain areas reduce the effectiveness of electronic reporting. Socialization and education programs remain crucial for shaping taxpayers’ behavioral beliefs, while support from tax authorities and the social environment strengthens subjective norms that encourage compliance. Perceived behavioral control is influenced by the availability of technical assistance, the ease of using the system, and strict enforcement of tax sanctions. The study concludes that the successful implementation of e-Filing requires an integrated approach that strengthens knowledge, accessibility, system quality, and enforcement to enhance overall taxpayer compliance in Ambon City.